Research of Training Loads of Basketball Players - Victor Koryahin; Oksana Blavt; Volodymyr Prystynskyi; Volodymyr Stadnyk (OVS LLC, 2021)
The study objective is to identify physiological indicators for the systematization of basketball players' special exercises and limit values of physiological indicators with sufficient "distinctive power" in each of the allocated training load ranges. Materials and methods. The study used empirical methods of measuring heart rate during competitions, pulmonary ventilation values, О2 consumption during physical work, О2-debt, "excess" CО2 emissions and individual pulse rates, methods of mathematical statistics. Results. Relationships between the level of physical activity and physiological shifts in the body of basketball players have been established. It is revealed that indicators of pulmonary ventilation can be used to control the training effect of aerobic exercise. Exercises of anaerobic glycolytic orientation have been shown to have the most pronounced effect on the body of basketball players. There are certain mean and limit values for different physiological parameters, characteristic of different ranges of training loads. Conclusions. It is established that in assessing the urgent training effect of special exercises of basketball players, different physiological indicators have different "distinguishing power". Based on the results of the study, it is proposed to systematize the special exercises of basketball players according to the ranges of training loads by the nature of their training effect.